The impact of radome on the GPS observation - Zulkarnaini Mat Amin, 1961-; Wan Abd. Aziz Wan Mohd. Akib; Tan, Han Yeong; Zuhaidah Nordin; International Symposium and Exhibition on Geoinformation (2005 : Pulau Pinang) (Skudai : Universiti Teknologi Malaysia, 2005)
13